2017
DOI: 10.1037/pac0000222
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-war and post-war intergroup contact on intergroup relations and mental health: Evidence from a Bosnian sample.

Abstract: Using a sample of Bosnian adults (N ϭ 381) we investigated the association between intergroup contact, measures of intergroup relations, and mental health. Structural equation models with latent variables showed that postwar contact had beneficial effects, being positively related to outgroup trust and intergroup forgiveness, and negatively associated with social distance. Moreover, postwar contact had indirect effects on reduced morbidity and posttraumatic stress disorder symptoms via increased intergroup for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 38 publications
3
33
1
Order By: Relevance
“…Specifically, positive extended contact before the war was positively associated with forgiveness and apology, positive extended contact during the war with support for financial compensation, and positive extended contact after the war with apology. These results extend the previous research on intergroup contact in post‐conflict settings by showing that positive intergroup relations in the aftermath of war may not only be improved by pre‐war direct contact experiences (Paolini et al, ; Voci et al, ) but also through pre‐war intergroup experiences of family members. This is particularly important since in many post‐conflict societies current intergroup contact may not be feasible, and so the time before the conflict may be the only source of positive intergroup encounters.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Specifically, positive extended contact before the war was positively associated with forgiveness and apology, positive extended contact during the war with support for financial compensation, and positive extended contact after the war with apology. These results extend the previous research on intergroup contact in post‐conflict settings by showing that positive intergroup relations in the aftermath of war may not only be improved by pre‐war direct contact experiences (Paolini et al, ; Voci et al, ) but also through pre‐war intergroup experiences of family members. This is particularly important since in many post‐conflict societies current intergroup contact may not be feasible, and so the time before the conflict may be the only source of positive intergroup encounters.…”
Section: Discussionsupporting
confidence: 87%
“…To examine the pattern of associations between extended contact at different time points and post-war reconciliation, we asked participants about the experience of their parents and grandparents with former adversary before, during, and after the war. A recent study on direct contact showed that positive direct intergroup contact in the past can promote positive intergroup relations in the present Voci, Hadziosmanovic, Hewstone, Cakal, & Veneziani, 2017).…”
Section: Extended Intergroup Contactmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Bagci and Turnuklu (under review) found that positive contact was directly and positively related to psychological well‐being among ethnic minorities. Voci, Hadziosmanovic, Cakal, Veneziani, and Hewstone () demonstrated post‐war contact to decrease post‐traumatic stress disorder symptoms among Bosnians. Bagci, Turnuklu, and Bekmezci (under review) demonstrated that disabled people's supportive and close friendships with nondisabled people were related to higher psychological well‐being through increased empowerment and social integration.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the researcher conducted this case study with those eleven respondents. All participants understood that the previous war between Indonesia and Dutch could ignite the intergroup problem (Kteily, Hodson, & Bruneau, 2016;Vedder et al, 2017;Voci & Hewstone, 2017) Case 1 In case number one, the main subject was referred to as "Odo" together with his eight friends. Odo had been living in Utrecht for more than five years.…”
Section: Resultsmentioning
confidence: 99%